Preparation and Comparison Between Bi2WO6 and ZnO Photoanodes in Dye-sensitized Solar Cells - Buagun Samran; Sumneang Lunput; Saranyoo Chaiwichian (Materials Research)
This study presents a comparative analysis of two photoanode materials such as bismuth tungstate (Bi2WO6) and zinc oxide (ZnO) for application in dye-sensitized solar cells (DSSCs). The Bi2WO6 and ZnO films were coated onto fluorine-doped tin oxide (FTO) glass substrate via the doctor blade method. The film samples were characterized by using XRD, SEM, TEM, XPS, FT-IR and UV-Vis-NIR techniques. The photovoltaic performance of DSSCs using MO and RhB dyes as sensitizers was assessed under solar light irradiation. Results revealed that Bi2WO6 and ZnO film photoanodes sensitized with MO dye showed superior photovoltaic efficiency compared to when sensitized with RhB dye. Moreover, the ZnO film photoanode achieved an efficiency of 1.24%, outperforming the Bi2WO6 film photoanode which had an efficiency of 0.85% under similar conditions. A probable mechanism for photogenerated electron transfer and charge carrier separation in DSSCs was proposed.